Peningkatan keterampilan menyimpulkan melalui penerapan model problem-based learning dalam pembelajaran ips pada peserta didik kelas IV sekolah dasar - Boby Devananda; Siti Istiyati; Yulianti Yulianti (Didaktika Dwija Indria, 2020)
Abstract. The purpose of this research is for improving the concluding skills on social science learning for fourth grade students of SDN Tunggulsari II Surakarta in the 2019/2020 academic year using cooperative learning type Problem-based Learning. This classroom action research consist of two cycles, each cycle includes two meeting, and each meeting had 4 stages that is planning, action, observation and reflection. Subject and data source in this research is teacher and 30 students of VI SDN Tunggulsari II. The research uses collection and teachnique through observation, interviews, concluding skills test, and documentation. The data validity used in content validation. The data analysis teachnique used is an interactive analysis model. The relust of this research after use the action was increased from the first condition 55,03 (20%), 72,9 (43,33%) in the first cycle, and 79,6 (80%) in the second cycle. The conclusion in this research based on the result are cooperative learning type PBL can improve concluding skills on social science learning learning for fourth grade elementary school students.